Material de reciclaje para el desarrollo cognitivo en niños de Educación Inicial II - Aguilar Espinosa, Sandra Katherine (2025)
In summary, this research explores the contribution of recycling materials in cognitive development in children in Early Childhood Education II at the Juan E Verdesoto Basic Education School. The research is framed by three types of research, descriptive, field and documentary. Teachers are not applying teaching strategies based on recycling material such as cardboard, bottles, covers, lids, which limit the development of essential skills in children such as attention, concentration, memory and problem solving, which are key aspects for good academic and cognitive performance, so this research has as its main objective to understand how the use of these materials can promote skills such as concentration, creativity, attention, memory and problem solving. The methodology will be used where the non-experimental design is chosen, followed by the qualitative approach, the phenomena are studied as they occur in their natural context, as a data collection technique, an interview and observation were applied, as well as instruments such as the question questionnaire and the observation sheet. As a result, recycled materials are of great importance as they stimulate the cognitive and creative development of the infant, the results contribute to the great interest and motivation of the students, promoting learning through recreational and playful activities. In conclusion, the use of recycled materials in pedagogical activities is shown to be an effective strategy to promote cognitive development with children. By stimulating autonomy, teamwork and problem solving